Tính tổng: A = 12 + 22 + 32 + … + n2.
Câu hỏi:
Trả lời:
A = 12 + 22 + 32 + … + n2
A = (1 . 2 – 1) + (2 . 3 – 2) + (3 . 4 – 3) + … + [n(n + 1) – n]
A = [1 . 2 + 2 . 3 + … + n(n + 1)] – (1 + 2 + 3 + … + n)
Đặt B = 1 . 2 + 2 . 3 + … + n(n + 1) và C = 1 + 2 + 3 + … + n.
+ Ta tính tổng B:
B = 1 . 2 + 2 . 3 + 3 . 4 + ... + n(n + 1)
Nhân 2 vế của B với 3 ta có:
3B = 1 . 2 . 3 + 2 . 3 . 3 + 3 . 4 . 3 + ... + n(n + 1) . 3
3B = 1 . 2 . 3 + 2 . 3 . (4 – 1) + 3 . 4 . (5 – 2) + ... + n(n + 1)[(n + 2) – (n – 1)]
3B = 1 . 2 . 3 + 2 . 3 . 4 – 1 . 2 . 3 + 3 . 4 . 5 – 2 . 3 . 4 + ... + n(n + 1)(n + 2) – (n –1)n(n + 1)
3B = n (n + 1)(n + 2)
B =n(n+1)(n+2)3
+ Ta tính tổng C:
C = 1 + 2 + 3 + … + n
Nhân 2 vế của C với 2 ta có:
2C = 1 . 2 + 2 . 2 + 3 . 2 +…+ n . 2
2C = 1 . 2 + 2(3 – 1) + 3(4 – 2) +…+ {n.[(n + 1) – (n – 1)]}
2C = 1 . 2 – 1 . 2 + 2 . 3 – 2 . 3 + 3 . 4 – … – n(n – 1) + n (n + 1)
2C = [1 . 2 – 1 . 2] + [2 . 3 – 2 . 3] + [3 . 4 – 3 . 4] + … – n(n – 1) + n(n + 1)
2C = 0 + 0 + 0 + …. + n.(n + 1)
2C = n.(n + 1)
C = n(n+1)2
Do đó, A = B – C = n(n+1)(n+2)3−n(n+1)2
=2n(n+1)(n+2)6−3n(n+1)6.
=2n(n+1)(n+2)−3n(n+1)6
=n(n+1)[2(n+2)−3]6
=n(n+1)(2n+1)6
Vậy A =n(n+1)(2n+1)6 .